Effectiveness of the SIGER-U Pocket Book (Seru Toothbrush) in Improving Toothbrushing Skills Among Kindergarten Children - Tarina Tarina; Santi Oktavia; Dewi Yuliana (Genius Journal, 2026)
Objective: Dental and oral health problems in preschool-aged children still occur frequently, one of which is caused by poor teeth brushing skills. Preschool-aged children are not yet able to maintain oral hygiene independently, so they are at risk of experiencing dental caries. Promotive and preventive efforts are needed through health education using media that suits the characteristics of children. The Siger-U Pocket Book (Fun Toothbrush) is a dental health education medium that is prepared in a simple, visual and interesting way to help children understand and practice the correct way to brush their teeth. This study aims to determine the effect of using the Siger-U Pocket Book (Fun Toothbrush) on improving toothbrushing skills in Citra Melati Kedaton Kindergarten children in Bandar Lampung. Method: This research uses quantitative methods with a pre-experimental design using a one group pretest–posttest design. The research was carried out from 13 December 2025 to 05 January 2026 at Citra Melati Kindergarten in Bandar Lampung. The research population was all 38 Citra Melati Kindergarten children, with a sample of 38 children using a total sampling technique. The research instrument is a toothbrushing skill observation sheet with eight assessment steps. Data analysis was carried out using the Wilcoxon Signed Rank Test after carrying out the Shapiro–Wilk normality test with a significance level of 5%. Result The results of the study showed that there was an increase in children's tooth brushing skills after being given the Siger-U Pocket Book intervention. The Wilcoxon test results show a p-value of 0.000 (p ≤ 0.05), which means that there is a significant effect of using the Siger-U Pocket Book on improving teeth brushing skills. Conclusion: The conclusion of this research is that the Siger-U Pocket Book has a significant effect on improving the toothbrushing skills of preschool children. It is recommended that the Siger-U Pocket Book be used as a medium for dental health education in kindergartens and in dental and oral health promotion activities.